Research on extrusion welding of dissimilar magnesium alloys: Mg–Al–Zn and Mg–Gd - Jieyu Li; Shengwen Bai; Zhihua Dong; Yan Yang; Jiangfeng Song; Weijun He; Guangsheng Huang; Bin Jiang (Journal of Materials Research and Technology)
In this study, the extrusion welding behavior of dissimilar Mg alloys, specifically Mg–Al–Zn and Mg–Gd, was investigated. Extrusion welding experiments were conducted using three combinations: AZ31 and Mg-1.5Gd (AG), AZ31 and AZ31 (AA), and Mg-1.5Gd and Mg-1.5Gd (GG), at different temperatures, accompanied by finite element (FE) simulations. The microstructures of the welding interfaces of the three types of sheets were examined, and the extrusion welding behavior of the AG sheets was analyzed by integrating the experimental and simulation results. The findings revealed that, as the extrusion temperature increased, the shear strength of all three types of sheets first increased and then decreased. The maximum shear strength of the AG sheets (120 MPa) was attained at 350 °C, whereas that of the AA (126 MPa) and GG (133 MPa) sheets was reached at 300 °C. Furthermore, the welding interface in the AG sheets induces shear strain, leading to the formation of fine grain bands near the interface and a gradient in the grain size in the Mg–Gd layer. These results offer new insights into the extrusion welding mechanisms of dissimilar Mg alloys.